MXenes in biosensing: Enhancing sensitivity and flexibility – A review of properties, applications, and future directions - Ali Mohammad Amani; Lobat Tayebi; Ehsan Vafa; Alireza Jahanbin; Milad Abbasi; Ahmad Vaez; Hesam Kamyab; Lalitha Gnanasekaran; Shreeshivadasan Chelliapan (Sensing and Bio-Sensing Research)
MXenes are a novel type of nanostructured material that has received a lot of attention for their potential applications in bioanalysis owing to their unique features. These materials, made from transition metal nitrides, carbides, or carbonitrides, have a number of advantages, including high hydrophilicity, a large surface area, strong metallic conductivity, superior ion transport capabilities, biocompatibility, and low diffusion barriers. Their surfaces are easily manipulated, making them more adaptable for a variety of applications, including biosensing. The outstanding properties of MXenes have attracted researchers of different fields, including renewable energy, fuel cells, supercapacitors, electronics, and catalysis. In the context of biosensing, MXenes are particularly noteworthy because of their layered structure and composition, which render them suitable for both electrochemical and optical biosensors. The high electrical conductivity and multilayered design of MXenes facilitate effective charge transport and the preservation of biological activity when biomolecules are attached to their surfaces. This characteristic positions them as ideal candidates for the creation of sensitive and efficient electrochemical biosensors. Moreover, the inherent flexibility of MXenes allows for the development of sensors compatible with wearable technologies, presenting substantial opportunities for real-time, on-body detection of biomolecules. This review looks at various applications of MXenes in electrochemical and optical biosensing, with a focus on how they help improve sensor performance metrics like sensitivity, stability, and biocompatibility. It also discusses the obstacles and limitations that must be overcome to fully realize MXenes' potential in biosensor technology, such as issues with large-scale manufacturing, surface modification, and long-term stability. The review concludes by discussing future directions and advancements in this field.